The architecture of creditions: Openness and otherness - Davies, Oliver (Frontiers in Psychology, 2022)
‘Creditions’ are an important new idea within our contemporary understanding of the human. They potentially represent the unity of both humanistic and scientific ways of modelling the human. As such, ‘creditions’ offer a bridge between current thinking in science and the humanities and the development of a more powerfully integrated interdisciplinary hermeneutic. It is argued in this article that the questions posed by ‘creditions’ (as developed by Rüdiger Seitz and Hans-Ferdinand Angel) cannot be resolved through reduction but rather only through cohesive systematization. In contrast with coherence in conventional science, ‘credition-centred’ thinking finds expression in systemic ways. The complex humanity of the reflective subject resists reduction; and calls to be analysed in terms of sociality, the identification of ‘otherness’ and interactive engagement. In this context then a thinking which is attuned to complexity and to otherness has an important place in the expression of the social subject as a complex and relational self, in today’s world. These are not however social realities as we find them either in large-scale social schemata, or indeed in the intimacy of the face to face. Rather credition-centred learning falls between these two categories and is best described as ‘the productive knowledge of community’, where community is generated by productive enhancement and the embrace of otherness over time.